2016
DOI: 10.1016/j.ccell.2016.08.004
|View full text |Cite|
|
Sign up to set email alerts
|

T Cell Cancer Therapy Requires CD40-CD40L Activation of Tumor Necrosis Factor and Inducible Nitric-Oxide-Synthase-Producing Dendritic Cells

Abstract: SUMMARY Effective cancer immunotherapy requires overcoming immunosuppressive tumor microenvironments. We found that local nitric oxide (NO) production by tumor-infiltrating myeloid cells is important for adoptively transferred CD8+ cytotoxic T cells to destroy tumors. These myeloid cells are phenotypically similar to inducible nitric oxide synthase (NOS2)- and tumor necrosis factor (TNF)-producing dendritic cells (DC), or Tip-DCs. Depletion of immunosuppressive, colony stimulating factor 1 receptor (CSF-1R)-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
108
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 53 publications
3
108
1
Order By: Relevance
“…Our study illustrates that adoptive cell therapy with CTLs increases the frequency of tumor DCs in both WT and Zbtb46 bone marrow chimeras, presumably by augmenting proinflammatory signals in the TME (25). In WT bone marrow chimeras, DC2 and DC3 increased, whereas the frequency of DC1 remained constant.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Our study illustrates that adoptive cell therapy with CTLs increases the frequency of tumor DCs in both WT and Zbtb46 bone marrow chimeras, presumably by augmenting proinflammatory signals in the TME (25). In WT bone marrow chimeras, DC2 and DC3 increased, whereas the frequency of DC1 remained constant.…”
Section: Discussionmentioning
confidence: 83%
“…As compared with DC1/DC2, DC3 showed a similar capacity to stimulate OT-1 CTLs, suggesting that iNOS expression per se may not reliably predict APC activity and CTL responses in vivo. Interestingly, Marigo et al (25) reported that CTLs stimulate tumor DCs to produce NO, which inhibited tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α, a well-known proinflammatory cytokine present in neurons and the glia, is involved in physiological and pathophysiological processes of the brain. 23,33,37,38 TNF-α acts as an effector molecule in brain development and is often involved in different signaling pathways to elicit the activation of macrophages and glial cells for neurotoxin production and to initiate the apoptosis/ death process in neurons. [39][40][41] Until now, the overall role of α α α α α α α α α α α α Figure 5 The levels of sOD, MDa, Il-4, Il-6, Il-8, Il-10, and NO in the rat brain tissue (n=10).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Research shows that TNF-α can prevent the death/apoptosis of neurons by a mechanism involving activation of transcription factor NF-κB, which induces the expression of Mn-SOD and Bcl-2. [22][23][24] The pharmacokinetics of TNF-α is characterized by an extremely short half-life (15-30 min) and low bioavailability. 25,26 Reports have concluded that it is difficult to control the dose of TNF-α preconditioning for treatment of BI/RI, and a large dose of TNF-α can result in significant side effects, including shock and death.…”
Section: Introductionmentioning
confidence: 99%